T-lymphocyte progenitors in man: phenotypic characterization of blood and bone marrow T-colony forming cells. - Triebel, F (1985)
Human T-lymphocyte cell precursors are driven to proliferate in vitro and to form T-cell colonies during incubation with a PHA-stimulated lymphocyte supernatant (P-SUP). By using cell affinity chromatography, we selected different populations of putative T-lymphocyte precursors in the blood and bone marrow. T-colony forming cells (T-CFC) were found in each of these different populations of cells with phenotypically immature cell surface markers: OKT11- cells or OKT4-/OKT8- cells in the blood and bone marrow, and OKT10+ or RFB-1+ cells in the bone marrow. Pretreatment with OKT3, together with a monoclonal anti-DR antibody and complement, did not abrogate the T-colony forming capacity. The OKT4-/OKT8- precursors were more radiosensitive (Do = 105 rads) than OKT4+, OKT8+ cells (Do = 360 rads) in their T-colony forming capacity. These results suggest that T-CFC could be induced to grow in agar from cells populations representing early steps of the T-cell lineage.